Preparation of Financial Statements Based on SAK EMKM In Small Micro Enterprises And Menengah (MSMEs) Fostered By The Department of Agriculture, Marine Affairs and Parepare City Fishery - Sri Rezky Handayani; Arfianty Arfianty; Yadi Arodhiskara (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
MSMEs are economic activities that play an important role in economic growth, maka if the MSME sector is disturbed then the national economy is also disturbed, As for the purpose ofthe study is 1). To find out the process of preparing financial reports for small and medium enterprises based on SAK EMKM on MSMEs